Physical and electrical properties of Li1+xTi2-xAlx(PO4)3 and Li1+2xTa1-xAlx+1(PO4)3 electrolytes - Kimpa, Mohammed Isah (2018)
Sodium superionic conducting materials (NASICON) are promising solid electrolytes for Li-ion rechargeable batteries. In this study, two compositions; lithium titanium aluminium phosphate (LTAP), Li1+xTi2-xAlx(PO4)3 (x = 0.0, 0.2, 0.6, 1.0) and lithium tantalum aluminium phosphate (LTaAP), Li1+2xTa1-xAlx+1(PO4)3 (0 ~ 0.5) solid electrolyte were synthesized via solid state reaction techniques at various sintering temperature ranging from 700 to 1000 °C for 8 and 12 h respectively. Lithium carbonate (Li2CO3), titanium dioxide (TiO2), aluminium dioxide (Al2O3), tantalum oxide (Ta2O5) and ammonium dihydrogen phosphate (NH4H2PO4) of high purity grade were used as the starting material. Physical properties of LTAP and LTaAP electrolyte show bulk density of 2.83 and 3.63 g/cm3 at 900 and 800 °C sintering temperature. XRD revealed major phase of LiTi2(PO4)3 NASICON structure and secondary phases (Ti4(PO5)3, TiO2 and AlPO4) co-exist in LTAP and LTaAP samples. FTIR shows presence of NASICON phosphate peaks which were dominated with vibration of PO4 ion in all prepared LTAP and LTaAP electrolytes. This also confirms the presence of LiTi2(PO4)3 in all of the samples. The ionic conductivity of solid electrolytes was analyzed with IS at room temperature. The highest conductivity was 1.06 x 10-4 and 9.854 x 10-6 S/cm for Li1.2Ti1.8Al0.2(PO4)3 and Li1.2Ta0.9Al1.1(PO4)3 electrolytes at room temperature. Conductivity behavior is enhanced when the sample was doped with aluminium, x = 0.2 for LTAP and x = 0.1 for LTaAP composition. The high ionic conductivity of LTAP-0.2 was supported by density data and lower impurity peaks, as reported in XRD. LTAP had better conductivity behavior compared to LTaAP composition which could be due to hard nature of tantalum in the stoichiometry ratio of LTaAP compound resulted into wide grain boundary and lower its conductivity. However, from ac conductivity analysis, the conductivity values for LTAP-0.2 and LTaAP-0.1 are within the range of 0 < s < 1.